The Effect of Emotional Blackmail on the Quality of Marital Relationships: The Mediating Role of Marital Burnout in Women Seeking Divorce - Shahi, Shirin; Rostamnezhad, Maryam (KMAN Counseling & Psychology Nexus, 2024)
This study aimed to investigate the effect of emotional blackmail on the quality of marital relationships among women applying for divorce, with marital burnout considered as a mediating variable. This research employed a descriptive-correlational design with an applied purpose. The statistical population included all women seeking divorce who referred to licensed pre-divorce counseling centers in Ramsar and Tonekabon between February and June 2024. A purposive sample of 210 participants completed three standardized questionnaires: Rahmat’s Emotional Blackmail Inventory (2019), Pines’ Marital Burnout Questionnaire (1996), and the Marital Relationship Quality Scale by Busby et al. (1995). Data were analyzed using SPSS 25 and AMOS 24. Normality was confirmed through the Kolmogorov–Smirnov test, and structural equation modeling (SEM) was used to assess the research model. The results revealed a significant negative relationship between emotional blackmail and marital relationship quality (β = -0.37, p < 0.01). Marital burnout was also significantly and negatively associated with relationship quality (β = -0.61, p < 0.01) and positively associated with emotional blackmail (β = 0.82, p < 0.01). The Sobel test confirmed the mediating role of marital burnout (Z = 6.685), and the Variance Accounted For (VAF) indicated that 57.5% of the total effect of emotional blackmail on relationship quality was explained through indirect effects, confirming partial mediation. Emotional blackmail significantly reduces marital relationship quality both directly and indirectly by increasing marital burnout. This highlights the destructive role of emotional manipulation in intimate relationships and underscores the importance of identifying and addressing emotional burnout as a key mechanism of relational decline.